ANALISIS SIFAT FISIK TANAH PADA TEGAKAN TANAMAN CENGKEH (EUGENIA AROMATICA L.) DI DESA LAULALANG KECAMATAN TOLITOLI UTARA KABUPATEN TOLITOLI PROVINSI SULAWESI TENGAH - Mawaddah, Mawaddah; Pagiu, Salapu; Monde, Anthon (AGROTEKBIS, 2018)
The purpose of this study was to determine the quality of soil physical properties in Clove stands (Eugenia aromatica L.) in Laulalang village, North Tolitoli Subdistrict, Tolitoli District, Central Sulawesi Province. This research was carried out from March to April 2018 which took place in Laulalang Village, North Tolitoli Subdistrict, Tolitoli Regency, Central Sulawesi Province. For the analysis of soil physical and chemical properties carried out in the Laboratory of Soil Science Unit, Faculty of Agriculture, Tadulako University, Palu. The method used in this study is a direct survey method in the field and continued with making a land unit map by way of overlapping a war map and land use map using the GIS Arc 10.4 application, so that there are 5 units of land with different slopes. The results showed that in the study area, the soil texture was dominated by dusty clay, organic matter was 1.44% (low), hydraulic conductivity was 5.12 cm-1 (medium), soil volume weight was 1.44 g cm-3(medium).